Control of cardiac chronotropic function in patients after heart transplantation: effects of ivabradine and metoprolol succinate on resting heart rate in the denervated heart - Rivinius, Rasmus; Helmschrott, Matthias; Ruhparwar, Arjang; Rahm, Ann-Kathrin; Darche, Fabrice Fernand; Thomas, Dierk; Bruckner, Thomas; Ehlermann, Philipp; Katus, Hugo; Dösch, Andreas (Clinical research in cardiology, 2018)
BackgroundPatients after heart transplantation (HTX) present with sinus tachycardia due to graft denervation. As elevated heart rates negatively affect survival, the aim of this study was to analyze the effects of ivabradine vs metoprolol succinate on heart rate, left ventricular (LV) mass and survival following HTX.MethodsThis observational retrospective single-center study assessed 84 patients continuously receiving either ivabradine (n = 40) or metoprolol succinate (n = 44) within 2 years after HTX. Patients with dual therapy (ivabradine and metoprolol succinate), other beta blockers, amiodarone, or digitalis were excluded. Patient characteristics, post-transplant medication, heart rates, LV mass, and survival were investigated.ResultsAnalysis of patient characteristics, immunosuppressive drug regimen, and post-transplant medication showed no significant differences between groups except for ivabradine and metoprolol succinate. Baseline heart rates differed not significantly between patients treated with ivabradine [87.0 beats per minute (bpm)] and metoprolol succinate (86.2 bpm; P = 0.6395). At 2-year follow-up, patients with ivabradine (76.7 bpm) had a significantly lower heart rate compared to baseline (P < 0.0001) and to metoprolol succinate (82.0 bpm; P = 0.0283). LV mass in patients receiving ivabradine was lower at 2-year follow-up compared to baseline (P = 0.0067) and patients receiving metoprolol succinate (P = 0.0179). Patients with ivabradine had a superior 2-year survival after HTX (P = 0.0049).ConclusionTreatment with ivabradine in patients within 2 years after HTX significantly reduced post-transplant heart rate and LV mass and was associated with a superior survival in comparison with patients receiving metoprolol succinate.